DẪN LIỆU BƯỚC ĐẦU VỀ THÀNH PHẦN LOÀI ẤU TRÙNG CÁNH LÔNG (TRICHOPTERA) Ở VƯỜN QUỐC GIA BẠCH MÃ TỈNH THỪA THIÊN HUẾ - Trung, Hoàng Đình; Sơn, Lê Trọng; Anh, Vũ Thị Phương (Vietnam Journal of Science and Technology, 2012)
PRELIMINARY DATA OF CADDISFLIES (INSECTA: TRICHOPTERA) INGREDIENT SPECIES IN BACH MA NATIONAL PARK, THUA THIEN HUE PROVINCE In this paper, we report the preliminary data of the Trichoptera and provide a list of caddisfly species, which are known for the first time in Bach Ma National Park. The research is carried out from February in 2009 to July in 2010 in water area of Bach Ma National Park, Thua Thien Hue province. The initial result of the caddisfly specimens collected during 17 months in six major places. As a result, a total of 22 species belonging to 15 genera, 10 families were recognized during the expeditions. The results showed total of 22 species belonging to 15 genera and 10 families that were found from seven sites in Bach Ma. Hydropsychidae is the most diverse with nine species; the second is Rhyacophilidae family with five species, while Brachycentridae, Hydrobiosidae, Leptoceridae, Odontoceridae, Psychomyiidae, Philopotamidae, Stenopsychidae and Xiphocentronidae have only one species of each. Basing on studied preliminary data of the caddisfly, the features of distribution and the features of ecological adapting with distribution of habitats, we devided species of aquatic insects present in Bach Ma National Park into two groups of distribution: the first group distributes in the running streams, and the other distributes in standing water areas.